Incidence and outcomes of healthcare-associated COVID-19 infections: significance of delayed diagnosis and correlation with staff absence. Issue 4 (December 2020) - Khonyongwa, K.; Taori, S.K.; Soares, A.; Desai, N.; Sudhanva, M.; Bernal, W.; Schelenz, S.; Curran, L.A.
Summary: Background: The sudden increase in COVID-19 admissions in hospitals during the SARS-CoV-2 pandemic of 2020 led to onward transmissions among vulnerable inpatients. Aims: This study was performed to evaluate the prevalence and clinical outcomes of healthcare-associated COVID-19 infections (HA-COVID-19) during the 2020 epidemic and study factors which may promote or correlate with its incidence and transmission in a Teaching Hospital NHS Trust in London, UK. Methods: Electronic laboratory, patient and staff self-reported sickness records were interrogated from 1 st March to 18 th April 2020. HA-COVID-19 was defined as COVID-19 with symptom onset within >14 days of admission. Test performance of a single combined throat and nose swab (CTNS) for patient placement was calculated. The effect of delayed RNA positivity (DRP, defined as >48 h delay), staff self-reported COVID-19 sickness absence, hospital bed occupancy, and community incidence of COVID-19 was compared for HA-COVID-19. The incidence of other significant hospital-acquired bacterial infections (HAB) was compared with previous years. Results: Fifty-eight HA-COVID-19 (7.1%) cases were identified. When compared with community-acquired admitted cases (CA-COVID-19), significant differences were observed in age ( P =0.018), ethnicity ( P <0.001) and comorbidity burden ( P <0.001) but not in 30-day mortality. CTNS-negative predictive value was 60.3%. DRP was associated with greater mortality ( P =0.034) and incidence of HA-COVID-19 correlated positively with DRP (R = 0.7108) and staff sickness absence (R = 0.7815). For the study period HAB rates were similar to the previous 2 years. Conclusions: Early diagnosis and isolation of COVID-19 patients would help to reduce transmission. A single CTNS has limited value in segregating patients into positive and negative pathways.